2015
DOI: 10.1590/1413-78522015230100513
|View full text |Cite
|
Sign up to set email alerts
|

The effects of laser treatment in tendinopathy: a systematic review

Abstract: Tendons have as main function transmit forces from the muscle to the bones. Tendinopathy is an inflammatory process that occurs in and around the tendon, when these are affected by some injury. Low level laser therapy consists in a local application of a monochromatic, coherent and short wavelength light. Its use began in 60's and since then several benefits for tendon injuries have been reported. The objective of this study is to collect the most recent studies about the use of laser on the tendinopathy treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This was also noted in mice models with pressure ulcers, where 670 nm light with a fluence of 5 J/cm 2 and varying power densities of 0.7–40 mW/cm 2 showed better response particularly at 8 mW/cm 2 than the rest [39]. Thus, cross analyses of several clinical trials have stated that the failure of LLLT is a result of too much or too little laser fluences that is appropriate to deliver cure on affected body parts [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…This was also noted in mice models with pressure ulcers, where 670 nm light with a fluence of 5 J/cm 2 and varying power densities of 0.7–40 mW/cm 2 showed better response particularly at 8 mW/cm 2 than the rest [39]. Thus, cross analyses of several clinical trials have stated that the failure of LLLT is a result of too much or too little laser fluences that is appropriate to deliver cure on affected body parts [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Because several literature reviews have not separately analyzed results based on laser wavelength or doses, it is possible that LLLT has a larger effect on tendon healing than is reported. 101 103 Detailed analysis including consideration of administration parameters may help to explain the currently heterogeneous results among contradictory reviews. For example, Bjordal et al demonstrated that LLLT modulates biological mechanisms of tendon repair in a dose-dependent manner, but an optimum dose has yet to be determined.…”
Section: Current Tendon-repair Therapiesmentioning
confidence: 99%
“… Note: Highlights the need for randomized control trials to provide consistency in results, a deeper understanding of tendon-cell biology, and the development of novel therapies that can better mimic natural physiology in a spatial and temporal manner. 69 , 88 94 , 97 100 , 103 114 , 117 , 118 , 121 , 122 …”
Section: Figurementioning
confidence: 99%
“…Low-level laser therapy (LLLT) uses light energy at levels low enough to not cause skin temperature increases, and there is some evidence for its ability to reduce inflammation and oedema, induce analgesia, and promote healing in a range of musculoskeletal pathologies. A small systematic review concluded that LLLT compared to placebo was an effective treatment option for tendinopathy 50 . There have also been promising results using low-intensity pulsed ultrasound in the treatment of Achilles tendinopathy 51 , but once again further research needs to be carried out to determine the long-term benefits and disadvantages of these alternative therapies.…”
Section: Managementmentioning
confidence: 99%